Here Comes Your King! Christ, Church and Nation in Malawi - Ross, Kenneth R. (Luviri reprints ;, 2020)
More than twenty years have passed since this book was first published yet its themes remain vital for understanding the way in which Christian faith is coming to expression in a context like Malawi. It begins with Christology, with the question of the identity of Jesus Christ that is perennially at the centre of the Christian theological task. For a century and more Malawians have been hearing the proclamation, "here comes your king!" This has struck a chord in millions of hearts as individuals, families and communities have named Jesus Christ as Lord. It has also posed the challenge of discovering what this Lordship means in every dimension of life. Much of the rest of the book pursues this question as it explores how church identity has been formed and consolidated, how the faith has been a resource for the nation at critical moments, and the ways in which the faith has shaped national identity and helped to meet political challenges--Foreword.